Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Kompos dengan Memanfaatkan Limbah Pelepah Sawit di Pematang Gubernur - Nuramal, Agus; Eka Putra, Rama Dani; zuliantoni, Zulian; Supardi, Nurul Iman (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2025)
Palm oil frond waste is a type of agricultural waste that is quite abundant in Pematang Gubernur Village, Muara Bangkahulu District, Bengkulu City. To date, this waste has not been optimally utilized and tends to be discarded, thus potentially polluting the environment. This community service activity aims to improve community knowledge and skills in processing palm oil frond waste into compost through hands-on training (learning by doing). The implementation method includes identifying partner needs, counseling, technical training in composting, practical assistance, as well as evaluation and follow-up. The results of the activity show an increase in community knowledge and skills in composting, the formation of compost products resulting from the training, the development of training modules, and the formation of community-based compost processing groups. This activity proves that utilizing palm oil frond waste can be an environmentally friendly solution while supporting community food security.